Pengaruh Kecemasan terhadap Hasil Tes Kebugaran Wasit Futsal - Fadilah, Roby; Imanudin, Iman; Zaky, Mohammad (Jurnal Simki Pedagogia, 2025)
This study aims to analyze the effect of anxiety on the results of the futsal referee fitness test. Anxiety is a mental factor that can affect physical performance, especially in situations that require accuracy and fast reactions. The method used is quantitative by giving questionnaires to participants before the fitness test consisting of several types of tests, including the sprint test, Coda test, and Ariet test. The results showed that there was no significant relationship between anxiety and the sprint test results (p = 0.052), indicating that anxiety did not directly affect the referee's sprint speed ability. However, there was a significant relationship with a positive direction between anxiety and the Coda test (p = 0.002, r = 0.431), meaning that the higher the level of anxiety, the more it affected the referee's performance in the agility test. Meanwhile, there was no significant relationship between anxiety and the Ariet test (p = 0.120), indicating that anxiety did not affect the referee's physical endurance. In conclusion, mental aspects, especially anxiety, can have an impact on the physical performance of futsal referees, especially in terms of agility. Therefore, in referee training, it is important to pay attention to anxiety management and mental readiness so that referees can perform optimally in leading the match.